The prevalence and root causes of delay in seeking healthcare among mothers of under five children with pneumonia in hospitals of Bahir Dar city, North West Ethiopia - Bantie, Getasew Mulat (BMC Pediatr, 2019)
BACKGROUND: Globally pneumonia is the leading cause of under-five child mortality. Several risk factors for pneumonia mortality have been identified, including delay in seeking health care. For successful reduction of delay in seeking healthcare, further evidence is crucial on its magnitude and factors associated with it in the country particularly in the study area. Therefore, this study aimed to determine the prevalence and root causes of delay in seeking health care among mothers of under-five children with pneumonia in hospitals of the Bahir Dar city, 2019. METHODS: A hospital-based cross-sectional study was conducted from March 15 to May 15, 2019 among 356 mothers of under-five children with pneumonia in hospitals of the Bahir Dar city. The study participants were selected by using a stratified sampling technique and data was collected through face to face interview. Binary logistic regression was used to identify the associated factors of delay in seeking healthcare. The P - value < 0.05 was considered statistically significant. Associations between outcome and exposure variables were expressed by the adjusted odds ratio with a 95% confidence interval (CI). RESULTS: A total of 356 mothers participated in the study yielded a response of 89.4%. The proportion of delay in seeking health care was 48.6%. Rural residence (AOR = 2. 3, 95% CI: 1.1, 4.9, seek healthcare in a governmental hospital (AOR = 3. 3, 95% CI: 1.8, 6.1), health care decision by mothers (AOR = 2. 9, 95% CI: 1.6, 5.4), poorest household (AOR = 2. 8, 95% CI: 1.1, 7.2), using self-medication (AOR = 7. 5, 95% CI: 3.8, 14.7), using traditional medicine before healthcare-seeking (AOR = 2. 7, 95% CI: 1.4, 5.1), and no information about early healthcare-seeking for childhood pneumonia treatment (AOR = 5. 1, 95% CI: 2.8, 9.1) were the identified determinants significantly associated with delay in seeking healthcare among mothers of under-five children with pneumonia. CONCLUSION: This study showed that nearly half of the mothers delayed in seeking healthcare. Rural residence, healthcare seeking at government hospitals, healthcare decision by mothers, poorest household, using self-medication, using traditional medicine before health care seeking, and lack of information about early healthcare-seeking were factors associated with a delay in seeking healthcare for under-five children with pneumonia. Hence, the government and other concerned stakeholders should give due emphasis to tackle on the identified causes of delay in seeking health care for the under five children with pneumonia.